Design of a Hydrostatic Spindle and Its Simulation Analysis with the Application to a High Precision Internal Grinding Machine - Youyun Shang; Kai Cheng; Hui Ding; Shijin Chen (Machines, 2022)
Hydrostatic thrust bearings are the core part of the hydrostatic spindle, which is widely used in high precision grinding machines. In this paper, the viscosity-temperature (v-t) characteristics of hydrostatic oil are systematically investigated, which is essential for improving the performance of the hydrostatic thrust bearing and the spindle working at high pressure and high rotational speed. Based on the computational fluid dynamics (CFD) simulation developed, the performance variation rules of thrust bearing surface are established while changing the oil supply pressure. It is found that the bearing capacity and temperature are obviously affected by varying viscosity-temperature characteristics, which have significant fluctuation phenomenon at the orifice. Furthermore, the turbulence intensity of the taper hole is found the least factor by analyzing four kinds of commonly used orifice type configurations. Finally, comparing the simulation and experimental results, the v-t model developed is proofed well matching with the experiment. The model can provide a basis for accurate design and analysis of hydrostatic thrust bearings and consequently the effective design and analysis of the hydrostatic spindle for high precision grinding machine.